Psychology for beginners! Louw, DA P & Edwards, DJ A (eds) (1993) Psychology: An introduction for students in southern Africa. Johannesburg: Lexicon. - de la Rey, Cheryl (PINS-Psychology in Society, 2026)
As a Psychology 1 lecturer of perhaps too many years, I welcomed the news that an introductory textbook specifically targeted at southern African students, was available. After having to rely on American textbooks for several years, most Psychology 1 lecturers would wholeheartedly support the opening lines in the Preface that "there is a serious need for a new first-year university textbook in psychology written and produced in southern Africa." But what advantages are the users offered over and above being written and produced in southern Africa? Key issues for both teachers and students are: the contextualization of the content, accessibility of language, and the price.